Iran’s Intellectual Revolution - John Andrew Morrow (International Institute of Islamic Thought, 2009)
Iran’s Intellectual Revolution, by Mehran Kamrava, offers an overview of the three major political orientations that have evolved in Iran since the Islamic revolution of 1979, especially since the death of Khomeini in 1989. The first chapter examines the silent, and often not-so-silent, revolution that has taken place in Iran over the past few decades; the second and third chapters contextualize these emerging Iranian discourses; and the fourth, fifth, and sixth chapters focus on the religious conservative, religious reformist, and secular-modernist discourses. Chapter three surveys the religious conservative discourse of Khomeini, Khamenei, Montazeri, Mesbah Yazdi, Rafsanjani, and Amoli. The author focuses on issues of interpretation, emulation, and the rule of the jurist (both conditional and absolute), all of which are essential if one wishes to understand the country’s current internal conflict and the varying conceptions of Islamic government that exist ...